Discourse Interpretation of Public Policy in the Context of Enforcement of Foreign Arbitral Awards in Indonesia - Saraswati, AAA Nanda; Hidayat, Choirul (Faculty of Law, Universitas Brawijaya, 2019)
The use of the concept of